Optimal Cyclical Monetary Policy: Does Steady-State Inflation Matter? - Samuel Reynard (Swiss National Bank, Study Center Gerzensee, 2003)
In general equilibrium models, optimal cyclical monetary policy is usually derived around an optimal steady-state inflation level, which in most cases is zero or equal to the negative of the real interest rate. This paper examines whether and how different steady-state inflation levels and other steady-state distortions affect the optimal monetary policy response to shocks. This issue is first discussed in general terms. Then, a simple example is presented, where optimal policy can be procyclical or countercyclical depending on the steady-state inflation level. This paper suggests that both issues of the choice of inflation target and optimal cyclical monetary policy should be addressed simultaneously, as steady-state distortions influence the optimal reaction of monetary policy to shocks. More generally, the paper shows that assumptions about steady-state distortions affect the derived optimal cyclical policy.
Keywords: 330